2013
DOI: 10.5897/ajar2013.6732
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rice straw treatment on feed intake, rumen fermentation and milk production in lactating dairy cows

Abstract: This experiment was conducted to investigate the effect of urea and urea-calcium hydroxide treated rice straws on feed intake, rumen fermentation and milk production in lactating dairy cows. Three multiparous Holstein crossbred dairy cows, mid-lactation with 365 ± 30 kg BW, were randomly assigned to receive three kinds of rice straw according to 3 × 3 Latin square design: untreated (T1), 2 × 2% ureacalcium hydroxide treated (T2) and 3% urea treated (T3). Based on the present findings, urea-calcium hydroxide co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 28 publications
3
8
0
3
Order By: Relevance
“…Crabtree-negative or -positive yeast has no effect on the dry matter intake (DMI). Our results showed that the DMI (range from 2.6 to 2.8 %BW) was similar to previous experiments, which is that feeding separate ensiled RS with a concentrate diet to dairy cows creates a DMI range from 2.5 to 3.2 %BW 42,43 . Generally, the amount of RS that an animal intakes daily is limited to around 2.0 % BW or less BW 44 .…”
Section: Feed Intake Nutrient Intake and Nutrient Apparent Digestibsupporting
confidence: 90%
“…Crabtree-negative or -positive yeast has no effect on the dry matter intake (DMI). Our results showed that the DMI (range from 2.6 to 2.8 %BW) was similar to previous experiments, which is that feeding separate ensiled RS with a concentrate diet to dairy cows creates a DMI range from 2.5 to 3.2 %BW 42,43 . Generally, the amount of RS that an animal intakes daily is limited to around 2.0 % BW or less BW 44 .…”
Section: Feed Intake Nutrient Intake and Nutrient Apparent Digestibsupporting
confidence: 90%
“…The latter results emphasize that pelleting TMR for lactating cows can be detrimental and reinforces the need to account for physically effective NDF during diet formulation. Additional trials examining replacement of concentrates or mixtures of Kung and Huber, 1983;Brown et al, 1990;Kendall et al, 2009 Urea Leaver and Hill, 1995;Hameleers, 1998;Prasad et al, 1998;Wanapat et al, 2009Wanapat et al, , 2013Mapato et al, 2010 Ammonia-fiber expansion Caution is needed when comparing the data because different forages or TMR proportions and components were treated with the technologies in the studies. These effects were associated with greater kernel breakage and starch digestibility for shredlage than conventionally processed corn.…”
Section: Mechanical Processingmentioning
confidence: 99%
“…Penambahan dengan urea paling umum digunakan untuk peningkatan nilai nutrisi pada pakan basal dengan kualitas rendah karena penanganannya sederhana, risiko rendah, mudah didapat dan harganya murah (Caneque et al, 1998;Yin et al, 2010;Ahmed and Babiker, 2015). Wanapat et al (2013) menunjukkan bahwa perlakuan jerami padi dengan menggunakan kombinasi 2% Urea-kapur atau 3% urea tunggal mampu meningkatkan asupan bahan kering, kecernaan nutrien, ekologi rumen dan produksi susu pada sapi perah Holstein crossbred. Khampa et al (2006) menyatakan bahwa kombinasi konsentrat yang mengandung cacahan singkong (cassava) (DM 75%) dengan urea 4% dan ditambah dengan sodium Dl-malate 20 g/hari mampu meningkatkan ekologi rumen dan sintesis protein mikroba dalam rumen sapi Friesian-Holstein crossbred laktasi pertama.…”
Section: Peran Urea Dalam Pening-katan Nilai Nutrisiunclassified